Physiological Functions of Thiol Peroxidases (Gpx1 and Prdx2) during Xenopus laevis Embryonic Development - Hongchan Lee; Na Young Lee; Youni Kim; Hong-Seok Choi; Tayaba Ismail; Hong-Yeoul Ryu; Dong-Hyung Cho; Zae Young Ryoo; Dong-Seok Lee; Taeg Kyu Kwon; Tae Joo Park; Taejoon Kwon; et al. (Antioxidants, 2021)
Glutathione peroxidase 1 (Gpx1) and peroxiredoxin 2 (Prdx2) belong to the thiol peroxidase family of antioxidants, and have been studied for their antioxidant functions and roles in cancers. However, the physiological significance of Gpx1 and Prdx2 during vertebrate embryogenesis are lacking. Currently, we investigated the functional roles of Gpx1 and Prdx2 during vertebrate embryogenesis using Xenopus laevis as a vertebrate model. Our investigations revealed the zygotic nature of gpx1 having its localization in the eye region of developing embryos, whereas prdx2 exhibited a maternal nature and were localized in embryonic ventral blood islands. Furthermore, the gpx1-morphants exhibited malformed eyes with incompletely detached lenses. However, the depletion of prdx2 has not established its involvement with embryogenesis. A molecular analysis of gpx1-depleted embryos revealed the perturbed expression of a cryba1-lens-specific marker and also exhibited reactive oxygen species (ROS) accumulation in the eye regions of gpx1-morphants. Additionally, transcriptomics analysis of gpx1-knockout embryos demonstrated the involvement of Wnt, cadherin, and integrin signaling pathways in the development of malformed eyes. Conclusively, our findings indicate the association of gpx1 with a complex network of embryonic developmental pathways and ROS responses, but detailed investigation is a prerequisite in order to pinpoint the mechanistic details of these interactions.